2014
DOI: 10.1039/c4ra02053g
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electronic properties of tungsten nanoclusters by DFT and basin-hopping calculations

Abstract: The structural and electronic properties of small tungsten nanoclusters Wn (n = 2–16) were investigated by density functional theory (DFT) calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Higher impurity levels will also increase the heterogeneous nucleation density. Additionally, the breakdown of the molecular precursors in chemical vapor deposition (CVD) and metal-organic chemical vapor deposition (MOCVD) requires a high activation energy, slowing down the growth process [60][61][62]. All of these modifications result in a 'shifting' of the experimental conditions to a region of higher temper ature and a higher flux (pressure), yet the underlying concepts remain the same as described throughout this work.…”
Section: Order Of Magnitude Improvement In Grain Size and Path To Lar...mentioning
confidence: 97%
See 1 more Smart Citation
“…Higher impurity levels will also increase the heterogeneous nucleation density. Additionally, the breakdown of the molecular precursors in chemical vapor deposition (CVD) and metal-organic chemical vapor deposition (MOCVD) requires a high activation energy, slowing down the growth process [60][61][62]. All of these modifications result in a 'shifting' of the experimental conditions to a region of higher temper ature and a higher flux (pressure), yet the underlying concepts remain the same as described throughout this work.…”
Section: Order Of Magnitude Improvement In Grain Size and Path To Lar...mentioning
confidence: 97%
“…with the reaction energy diagram shown in figure 2(b) [60]. In this study, only atomic precursors are included, since the strong binding energy of clusters of the metal or chalcogen requires an overly high activation energy (5.44 eV for W-dimers and 4.64 eV for Se dimers) to participate in the epitaxial process [61,62]. Atoms arriving at the substrate surface, rather than being reflected back into the ambient, have a probability of being adsorbed on the surface.…”
Section: Kinetics and Thermodynamics Of Nucleus Formation And Critica...mentioning
confidence: 99%
“…In general, point defects can increase average bond length and thus result in reduction in elastic modulus . Recent theoretical calculations and simulations suggested that the elastic moduli of many NWs decreased significantly with the increase in vacancy densities, including SiC, GaN, Si, W, Ag, Au and Cu . Experimental results also indicated that vacancies might be one of the important reasons for the relatively low modulus values of the NWs.…”
Section: Mechanical Characterization Of Nwsmentioning
confidence: 99%
“…Now we discuss the nucleation mechanism without a pre‐seeding strategy. In a common thermal CVD, that is, WSe 2 growth from the reaction of WO x and Se vapors, the homogeneous nucleation 40 occurs with the incorporation of W clusters 69 and Se clusters 70 . Such a nucleus formation requires a complicated process, including the precursor decomposition, atom adsorption/desorption, adatom diffusion, adatom pinning at defect sites, bonds formation between adatoms, and clustering 71 …”
Section: Discussionmentioning
confidence: 99%